Digital Citizenship Infrastructure to Foster the Reinforcement of National Identity in Indonesia - Candra, Alif Aditya; Suryadi, Karim; Rahmat, Rahmat; Nurbayani, Siti (Kultura-Społeczeństwo-Edukacja, 2021)
This study was to discuss and overview the infrastructure of digital citizenship in fostering the reinforcement of national identity in Indonesia. This study was prompted by a problem in the development of digital citizenship infrastructure, which could be an instrument in fostering national identity in Indonesia. The process of forming a national identity could be emphasized through various platforms in the digital citizenship infrastructure, so that the internalization of national values among Indonesian citizens could strengthen their identity as such. This study took the form of qualitative research with a phenomenological approach, constructing theories and phenomena concerning the infrastructure of digital citizenship in Indonesia. The results showed that the infrastructure of digital citizenship reinforced national identity in Indonesia in three ways, namely: 1) internalizing awareness of digital literacy through Citizenship Education learning, 2) implementing Habituation of national identity values in the digital citizenship infrastructure, and 3) running digital forums that could reinforce the digital citizenship infrastructure and strengthen national identity